In situ generated hypoiodous acid in an efficient and heterogeneous catalytic system for the homo-oxidative coupling of thiols - Ghorbani-Choghamarani Arash; Nikoorazm Mohsen; Azadi Gouhar (Journal of the Serbian Chemical Society, 2013)
Supported hydrogen peroxide on polyvinylpolypyrrolidone (PVPH2O2), silica sulfuric acid (SiO2-OSO3H) and catalytic amounts of potassium iodide (KI) has been developed as a heterogeneous medium for the rapid oxidative coupling of thiols into symmetrical homodisulfides. This oxidizing system proceeds under extremely mild conditions and gives no other oxidized side products.